Determinasi Pengaruh Populasi Walang Sangit (Leptocorisa oratorius Fabricius) terhadap Hasil Gabah Padi Sawah di Desa Kimak, Kecamatan Merawang, Kabupaten Bangka - Winarsi Winarsi; Sitti Nurul Aini; Rion Apriyadi (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2018)
Rice crops are the main source of staple food for the Indonesian people, as well as in the Bangka Belitung province. The cultivation of rice crops is still through various obstacles, such as the attack of Leptocorisa oratorius Fabricius, which attacks the rice plants after flowering by sucking the grain. The aim of this study was to know the effect of L.oratorius population on the rice yield, to know the number of L. oratorius that can decrease the 15% paddy yield and to know the percentage of rice loss based on the number of L. oratorius population in the Kimak village, Merawang district, Bangka regency. The research was conducted on November 2017 to January 2018 on paddy field in Kimak village. This research used experimental method with Completely Randomized Design (CRD) wich consist of 8 treatments and 2 replications. The treatment was the differences L.oratorius population. Consist of: without L.oratorius, 2 L.oratorius, 3 L.oratorius, 4 L.oratorius, 5 L.oratorius, 6 L.oratorius, 7 L.oratorius and 8 L.oratorius. The result showed that the number of L. oratorius has significant effect on rice yield, 3 population of L. oratorius per 50 cm x 50 cm able to reduce the rice yield by 15% and the percentage of yield loss at the treatment of 2 - 8 L.oratorius is about 10.97% up to 28.98%.